Люминесцентные характеристики тонких плёнок оксида цинка, полученных методом электрофореза [Articol] - Гоглидзе, Т.И.; Дементьев, И.В.; Задорожный, А.П.; Коваль, А.В.; Петренко, П.А.; Гашин, П.А. (CEP USM, 2012)
Показана возможность осаждения тонких однородных слоёв оксида цинка с низкой проводимостью электрофоретическим методом. Представлены результаты измерений фотолюминесценции тонких слоёв ZnO при температурах 300 К и 77 К.

Se arată posibilitatea depunerii straturilor subţiri omogene pe substraturi cu coeficient scăzut de conductibilitate prin metoda electroforetică. Sunt prezentate rezultatele măsurărilor de fotoluminescenţă a straturilor subţiri de ZnO la temperaturi de 300 şi de 77 K.

It is shown the possibility of thin homogeneous layers deposition on substrates with low conductivity by electrophoresis. The results of measurements of photoluminescence ZnO thin films at temperatures of 300 and 77 K are presented.
CARACTERISTICILE LUMINESCENTE ALE FILMELOR SUBŢIRI DE OXID DE ZINC OBŢINUTE PRIN ELECTROFOREZĂ
LUMINESCENCE CHARACTERISTICS OF THIN FILMS OF ZINC OXIDE OBTAINED BY ELECTROPHORESIS
Keywords: электрофоретический процесс; оксид цинка; люминесценция; proces electroforetic; oxid de zinc; luminescenţă; electrophoretic process; zinc oxide; luminescence